Platelet-rich plasma may accelerate diabetic wound healing by modulating epithelial/endothelial-mesenchymal transition through inhibiting reactive oxygen species-mediated oxidative stress - Li, Youan; Cheng, Biao; Tian, Ju (Frontiers in Bioengineering and Biotechnology, 2025)
The production of reactive oxygen species (ROS) and oxidative stress are central to the pathophysiology of diabetic wounds. This environment arises from the interplay of hyperglycemia, mitochondrial dysfunction, and chronic inflammation, leading to persistent damage. This hypothesis paper explores the therapeutic potential of Platelet-Rich Plasma (PRP) for accelerating diabetic wound healing. We specifically focus on PRP’s ability to modulate ROS and the key processes of Epithelial/Endothelial-to-Mesenchymal Transition (EMT/EndMT). PRP, rich in growth factors and functional platelet-derived mitochondria, shows promise in treating diabetic wounds by reducing oxidative stress and enhancing cellular processes crucial for healing. We propose that PRP accelerates healing through several interconnected mechanisms: (1) Reducing ROS production and alleviating oxidative stress; (2) Enhancing cell proliferation, migration, and angiogenesis; (3) Transferring healthy platelet-derived mitochondria to replace damaged host cell mitochondria, restoring energy metabolism; (4) Modulating cellular signaling pathways regulating ROS generation and scavenging systems, and subsequently impacts EMT/EndMT processes; and (5) Directly modulating EMT/EndMT dynamics. This hypothesis examines these proposed mechanisms and highlights future research priorities necessary to elucidate PRP’s precise mode of action and refine its clinical applications for diabetic wounds. Furthermore, the potential of PRP in treating other oxidative stress-related conditions warrants investigation.